2004
DOI: 10.1177/1470595804041527
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management in Greece

Abstract: This article investigates whether Human Resource Management (HRM) in Greece is maintaining its national character or whether it is converging towards a model that potentially clashes with the country’s traditional societal values. This issue fits in the wider convergence–divergence debate that has been the concern of many cross-cultural researchers. Using data collected from Greek firms and subsidiaries of multinationals (MNCs) located in Greece, we compare the two groups on specific HRM practices. The aim is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…However, these results are not consistent with our findings. Furthermore, HR planning, recruitment and performance appraisal are to a great extent congruent with the culture values of Greek society (Myloni et al, 2004).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, these results are not consistent with our findings. Furthermore, HR planning, recruitment and performance appraisal are to a great extent congruent with the culture values of Greek society (Myloni et al, 2004).…”
Section: Resultsmentioning
confidence: 89%
“…This will lead to improve the performance of employees and the whole company, since the employees will be satisfied with the practices that their company adopts. According to Myloni et al (2004) the results of how HRM practices reflect Greek national culture, could be helpful to multinational company"s decision makers in deciding which practices are more easily transferred into the Greek context and which practices have to be adapted this culture. Therefore, this study will help HR managers in their decisions of how such practices will be developed and what are they.…”
Section: Managerial Implicationmentioning
confidence: 99%
“…Other convergence theorists argue that the management function itself encompasses certain tasks and challenges that are universal in nature (Sanyal and Guvenli, 2004). As countries continue to develop their economies, the influence of national culture will tend to weaken, with firms moving toward a situation of 'competitive isomorphism' and managers making similar decision choices under similar circumstances, irrespective of their cultural identities and backgrounds (Myloni et al, 2004). The push toward convergence and the homogenization of management attitudes and beliefs seems to be getting increasingly stronger in recent times as a result of several economic phenomena such as the advent of the Internet, low cost telecommunications, deregulation and market reforms in many countries, and the creation of trading blocs (Friedman, 2005;Sanyal and Guvenli, 2004).…”
Section: Convergencementioning
confidence: 98%
“…Hofstede (1980) has shown that national culture may affect managerial behavior by influencing managers to espouse organizational values that are in conformity with the basic assumptions and beliefs they acquire and develop in their particular cultural contexts. Convergence theorists (e.g., Myloni et al, 2004), however, hold that as the pressures of globalization make themselves more evident, managers, irrespective of their cultural backgrounds, will be induced to adopt increasingly similar-looking value systems to meet global business challenges. The crossvergence viewpoint (e.g., Ralston et al, 1997) seeks to establish a middle ground between these two perspectives, positing that managers integrate their cultural perspectives with organizational imperatives to achieve a hybrid value system that evidences some aspects of both convergence and divergence.…”
Section: Introductionmentioning
confidence: 98%
“…In past years there has been a trend in countries in south Eastern Europe that shows a decrease in the number of companies where the head of HR was on the board of directors (Apospori et al, 2005). Another study comparing Greek firms with Multinational Companies' (MNC) subsidiaries in Greece reported that "HR planning was found to be less tightly linked with corporate planning in Greek firms than in MNC subsidiaries" (Myloni et al, 2004). Greek companies and their HR departments must strengthen their competency as strategic positioners.…”
Section: Business and Economic Researchmentioning
confidence: 99%